SHAH JUBAER’S POPULISM-LAW RECONCILIATION THEORY (PLRT) (Eureka Journal of Humanities and Social Research, 2026)
Populism presents both advantages and challenges to democratic governance. Although technology can enhance public engagement, it frequently challenges the limits of the rule of law and human rights. This idea centered research paper presents the Populism-Law Reconciliation Theory (PLRT), also known as the Shah Jubaer Theory, offering a comprehensive theoretical framework to harmonise populist demands with legal limitations. The study utilises comparative case studies, constitutional analysis, and normative assessment to implement the theory, providing resources for researchers and policymakers for years to come.